Tritium concentrations in coastal waters of the Far Eastern regions of the Russian Federation in the first year of controlled water discharge from the Fukushima–1 NPP (Preliminary results) - Repin, V. S.; Varfolomeeva, K. V.; Biblin, A. M.; Sednev, K. A.; Zelentsova, S. A.; Arkhangelskaya, G. V. (Radiacionnaâ gigiena, 2025)
The article presents results of a study on the tritium concentrations in seawater samples collected from September 2023 to June 2024 in coastal waters of the Far Eastern regions of the Russian Federation, including Primorsky, Kamchatka, and Khabarovsk Krais; Sakhalin and Magadan Oblasts; and the Chukotka Autonomous Okrug. The aim of the study is to determine the backgrounds values of tritium volume activity. The low-background liquid scintillation spectrometer-radiometer for alpha and beta radiation "Quantulus 1220” was used to determine the baseline tritium content in 185 seawater samples collected by specialists from the territorial bodies of Rospotrebnadzor in six subjects of the Far Eastern Federal District. The results indicate that the specific activity levels for the observation period from September 2023 to June 2024 were below 10.0 Bq/kg in samples collected from the coastal waters of the Far Eastern regions of the Russian Federation. The recorded tritium levels are significantly below the intervention level for drinking water (7600 Bq/L) as per NRB-99/2009, which applies to desalinated seawater.